Management of Operational Assistance for Educational Units Providing Special Sports Classes at Kendal 1 State Middle School - Raih Swastika; Nurkolis Nurkolis; Muhtarom Muhtarom (Sakura Digital Nusantara, 2026)
Purpose The government is introducing the BOSP as a strategic instrument to support the basic operational needs of schools. The provision of BOSP aims to expand access to education for the entire community. Methods This research used a qualitative approach. Data were collected through interviews, observation, and documentation, then analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of techniques and sources. Findings Planning has been carried out systematically, based on data, and involving various stakeholders through the preparation of the RKAS. The implementation of the use of BOSP shows a dualism of needs between regular classes and the KKO program. BOSP is effective in supporting basic education services, but has not been able to optimally accommodate the specific needs of the KKO program. BOSP financial reporting has been running well administratively and financially, marked by completeness of documents, timeliness, and the use of the ARKAS system. Supervision of BOSP use has been implemented through a multi-layer control system involving internal and external supervision. Research Implications This study implies that improving school quality can be strengthened through effective management of operational assistance funds for educational units, teacher development, and active parental involvement in school programs. Originality This study is original because it examines the management of operational assistance funds for educational units, emphasizing active partnerships between schools and school committees in improving school quality.